Fluid status and outcome in patients with heart failure and preserved ejection fraction. (1st March 2017) - Koell, Benedikt; Zotter-Tufaro, Caroline; Duca, Franz; Kammerlander, Andreas A.; Aschauer, Stefan; Dalos, Daniel; Antlanger, Marlies; Hecking, Manfred; Säemann, Marcus; Mascherbauer, Julia; Bonderman, Diana
Abstract: Background: Most heart failure with preserved ejection fraction (HFpEF) patients, at some point, present to an emergency department with typical symptoms of volume overload. Clinically, most respond well to standard diuretic therapy, sometimes at the cost of renal function. The study sought to define the prognostic significance of fluid status versus renal function in patients with HFpEF. Methods: One hundred sixty-two consecutive patients with HFpEF were enrolled in our prospective registry. Twelve patients with clinically overt decompensation were excluded. Fluid status at baseline was determined by bioelectrical impedance spectroscopy. The primary outcome measure was a combined end point consisting of hospitalization for heart failure and/or death for cardiac reason. Results: Mean age was 74.4 ± 8.4 years. Ninety-one (61%) patients were hypo- or normovolemic (relative fluid overload [Rel. FO] − 0.7 ± 5.7%) while 59 (39%) patients presented with fluid overload (Rel. FO 11.5 ± 2.7%). During a median follow-up of 24.3 months (interquartile range: 19.8–33.2), 34% of patients reached the combined end point. Multivariate Cox hazard analysis identified fluid overload (hazard ratio: 3.09; 95% confidence interval: 1.68–5.68; p < 0.001) as an independent predictor of adverse outcome. Patients with fluid overload and normal renal function showed a worse event-free survival compared to the subgroup with normohydration and impaired renal function (log-rank: p = 0.042). Conclusion: HFpEF patients with measurable fluid overload face a dismal prognosis as compared to euvolemic patients. Our data, while preliminary, suggest that patients with fluid overload may face a better outcome under continued fluid removal irrespective of changes in eGFR.